Working Hours, Sleep Disturbance and Self-Assessed Health in Men and Women: A Multilevel Analysis of 30 Countries in Europe - Mensah, Aziz; Toivanen, Susanna; Diewald, Martin (Frontiers in Public Health, 2022)
Objectives: This study examined the gender and cross-country differences in the relationship between working hours and self-assessed health among working men and women in Europe, and further explored the moderating role of sleep disturbance in the relationship. Methods: We used cross-sectional data from the 6th European Working Condition Survey on 14603 men and 15486 women across 30 countries in Europe. A multivariate logistic regression was applied to evaluate the relationship between working hours, sleep disturbance, and self- assessed health. In addition, we employed a two-stage multilevel logistic regression to assess the cross-country variations in the relationship between working hours and self-assessed health. Results: The study showed a slightly U-shaped relationship between working hours and less-than-good self-assessed health among working adults in Europe (<31 hours: aOR= 1.11; 95% CI: 1.00-1.25, 41-50 hours: aOR= 0.98; 95% CI: 0.84-1.15, and 50+ hours: aOR= 1.31; 95% CI: 1.07-1.59). However, working men had higher odds of reporting less-than-good self-assessed health as compared to women when they devote longer hours to paid work. The results further showed that there are cross-country variations in the association between working hours and less-than-good self-assessed health for both men and women, and that men had slightly lower variations as compared to women. Contrary to expectation, sleep disturbance did not moderate the relationship between working hours and less-than-good self-assessed health for both men and women in Europe. Conclusions: Although there are gender differences and cross-country variations in the association between working hours and less-than-good self-assessed health, sleep disturbance did not moderate the associations. These findings underscore the importance for strict work time regulation and generous work-family policies that may promote good working conditions and health.